O Direito das Crianças à Cidade apropriada como lugar de Liberdade e de (inter)Ação - Lopes, Frederico; Madeira, Rosa; Neto, Carlos (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In this article, we intend to discuss the children’s right to the city, assuming their role as "spatialists" who participate in the transformation of public spaces into meaningful places. The signs of change in the conditions and dispositions of society in relation to the presence of children, as a moving body that transits between unequal spaces, bring with them common territories to different disciplines that investigate childhood. Thus, we situate here the contribution that environmental psychology offers to the dialogue between areas of knowledge that problematize the physical and social invisibility of children and demand public policies for childhood as a condition of citizenship.